(untitled) (Proceedings of the World Disability & Rehabilitation Conference, 2019)
The aim of the research: Training in the inclusive higher school environment supposes joint training of higher school students with functional limitations, with other students in the integrated group. Social and psychological aspects of this phenomenon are studied insufficiently. In particular, the study of the acceptance degree of a student with disabilities in an inclusive group needs special attention. The indicators of sociometric status of a student with disabilities can help determine how well they are included in the team, how well they are accepted in the group. They also help assess the effectiveness of integration into the society at large. We should also note that the success of the actions of young people with disabilities will largely depend on their willingness to be active, able to initiate their own development, and act as a source and the cause of their own behavior, to overcome the negative impact of a situation of uncertainty, i.e. on the ability to self-determination. Methods: The sociometric test for the diagnostics of emotional links between members of the inclusive group, tests, studying personal self-actualization, method of studying the training motivation in higher school. Main results: we identified specificity of emotional interaction between the members of an inclusive group. The features of the personal potential of students with disabilities in comparison with healthy students were shown. Differences in educational motivation are presented. Conclusions: The position of a student with disabilities in the inclusive group has sociometric status of the one "who joined" or "isolate". That is the level of unity of inclusive groups is insufficient. The level of self-actualization of students in the inclusive groups depends on various conditions within the group and on the specific health problems. At the same time students with disabilities devote a driving position to motivation of acquiring knowledge and mastering profession in the hierarchy of motives.